[87] Articulated laparoscopic instruments: A new technology to overcome challenging uro-laparoscopic surgery - Mohammed Al-Ameedee (Taylor & Francis Group, 2018)
Objective: To demonstrate the use of articulated laparoscopic instruments. Technological development in laparoscopic instruments acts as a corner stone in facilitating and overcoming challenges in laparoscopic operations. The laparoscopic ureteric stent guider (LUSG) helps to overcome stenting difficulty. Other challenges like suturing, dealing with tissue areas in acute angles, changing the axis of the instrument from straight to right angle to give the same ability as robotic instruments, are overcome by an articulated instrument called the laparoscopic flexible forceps dissector (LFFD). Methods: From October 2010 to August 2016, 41 laparoscopic ureteric surgeries were performed. In all, 22 patients underwent laparoscopic pyeloplasty (14 females aged 10–55 and eight males aged 12–45 years). Laparoscopic ureterolithotomy was performed in 16 patients aged 10–38 years. Retrocaval ureter repair was performed in two male cases, with a mean age of 18 years. LUSG was used in 17 cases. From August 2016 to August 2017, the LFFD was used in laparoscopic uro-surgery; five cases of simple nephrectomy (three females and two males aged 38–62 years); three cases of radical nephrectomy (two males and one female aged 45–50 years); and laparoscopic pyeloplasty in one female aged 58 years. LFFD is designed to act like a robotic instrument but is hand-held and reusable. Results: The mean (range) operation time without LUSG was 2:42 (2:15–3:30) h and with LUSG was 2:15 (2:00–2:25) h, thus the LUSG decreased the operation time by 20–30 min, decreased ureteric over manipulation, and overcame stenting difficulties. The LFFD allows for easy manipulation of tissue and has the ability to flex and reach difficult tissue areas better than standard laparoscopic instruments with faster suture ligation and has movement ability that mimics the Da Vinci robotic instrument. Conclusion: Articulated laparoscopic instruments are the future of laparoscopic surgery, simple, affordable and more cost-effective than robotic surgery.